2013
DOI: 10.1590/s1983-14472013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Construção de uma tecnologia educacional para o ensino de enfermagem sobre punção venosa periférica

Abstract: The aim of the study was to describe the construction of a course on peripheral venipuncture using the Information and Communication Technologies. This is a methodological research, developed at the Federal University of Ceara from January to March 2012. The construction phases are: the analysis, design and development according to the theoretical framework of Galvis-Panqueva. In the analysis, objectives, content target audience, the study environment and technology infrastructure were delimited. During the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 7 publications
0
11
0
26
Order By: Relevance
“…The teacher must dominate the machine and take advantage of the potential of technology for the benefit of an education and a more creative, autonomous, collaborative and interactive learning, without the need to fear it. 6 The research warns that the nursing performance may be adversely affected if the information and communication technologies are improperly used. 18 By choosing to incorporate technology, it is imperative that educators have basic rules for good teaching practice and resource domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher must dominate the machine and take advantage of the potential of technology for the benefit of an education and a more creative, autonomous, collaborative and interactive learning, without the need to fear it. 6 The research warns that the nursing performance may be adversely affected if the information and communication technologies are improperly used. 18 By choosing to incorporate technology, it is imperative that educators have basic rules for good teaching practice and resource domain.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In this regard, several studies have shown that the application of technological resources, such as Moodle, applications, social networks, forums and Virtual Learning Environments, provide the acquisition of knowledge and cognitive skills to perform nursing procedures, increasing security and selfconfidence for their achievement by students. 5,6 In this study, the technology came in using a Software developed to be installed in a mobile electronic device such as mobile phones, Smartphones, and Tablets. This resource was chosen because it is a possible computational tool to be run on mobile phones, which is one of the most democratic means of access to digital inclusion today.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,14 O uso de tecnologias educacionais tem sido impulsionado por algumas vantagens como facilitar a compreensão de um conteúdo estudado, 15 respeitar o tempo de aprendizagem do aluno, 16 permitir ao estudante treinar quantas vezes sejam necessárias e a possibilidade do feedback. 15,16 No ensino de Enfermagem o apoio tecnológico pode conduzir o aluno a uma aprendizagem significativa, pois as interações computacionais facilitam a reflexão e o pensamento crítico. Soma-se, também, o fato de que o computador pode estimular a construção do conhecimento, conversação, articulação, colaboração e reflexão as quais facilitam a aprendizagem significativa.…”
Section: Resultsunclassified
“…The application and use of technology pro-ducts and computer-based technologies for health care is a permanent process in evolution [1]. This accelerated development of scientific and technological modernization has generated new ways of building knowledge and establishing relationships with the world of work.…”
Section: Introductionmentioning
confidence: 99%